2022
DOI: 10.1097/der.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Patch Testing: A Retrospective Review

Abstract: BackgroundPatch testing while taking systemic immunosuppressants is sometimes unavoidable. Methotrexate (MTX) is the immunosuppressant currently considered least likely to negatively impact patch testing.ObjectiveThe aim of the study was to characterize a cohort of patients patch tested while taking MTX.MethodsThis is a retrospective review of patients patch tested at the University of North Carolina Dermatology in Chapel Hill, North Carolina, from 2010 to 2019, comparing patch test results of patients taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…While some studies have shown that treatment with methotrexate is not likely to interfere with patch testing results, due to the fact that its effect is dose-dependent, it could have still made an influence on our results. 28 , 29 Furthermore, while other potential causes of psoriasiform lesions in the differential diagnosis could not be ruled out, it is crucial to note that patients included in this study exhibited a typical presentation of psoriatic lesions. Also, a larger cohort would enhance the accuracy of statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that treatment with methotrexate is not likely to interfere with patch testing results, due to the fact that its effect is dose-dependent, it could have still made an influence on our results. 28 , 29 Furthermore, while other potential causes of psoriasiform lesions in the differential diagnosis could not be ruled out, it is crucial to note that patients included in this study exhibited a typical presentation of psoriatic lesions. Also, a larger cohort would enhance the accuracy of statistical analysis.…”
Section: Discussionmentioning
confidence: 99%